Legal Review of Criminal Law on Children as Victims of Human Trafficking (Study of Decision Number: 1824/Pid.Sus/2023/PN.Mdn) - Marsally, Putri Ayu; Pratitis, Sugih Ayu; Harahap, Muslim (Civiliza Publishing, 2025)
Children are a vulnerable group that requires special legal protection, especially in cases of human trafficking. The research method used is normative juridical or library research, by analyzing library materials or secondary data relevant to the topic. This research is descriptive analytical, namely data obtained and processed and analyzed to provide a comprehensive picture of the legal regulations and law enforcement against children as victims of human trafficking as regulated in Article 2 and Article 3 of Law Number 21 of 2007 concerning TPPO and Article 455 - 257 of Law Number 1 of 2023 concerning the Criminal Code with data collection methods through document studies and interviews. Research Results Show that criminal law in Indonesia has strictly regulated the protection of children as victims of human trafficking, both through Law Number 35 of 2014 concerning Child Protection and Law Number 21 of 2007 concerning the Eradication of Criminal Acts of Human Trafficking, then in Decision Number: 1824 / Pid.Sus / 2023 / PN.Mdn Shows the role of law enforcement officers is quite significant in enforcing the law and providing justice for child victims, although there are still challenges such as evidence, protection of witnesses / victims, and psychological recovery of children after the incident.